Analisa Rancangan Perkuatan Lereng Sungai Tipe Gravitasi - Rohadi Budi Prasetyo, Slamet; Tria Saputri, Titis; Nurtjajaningtyas, Indra; Purnama Putra , Paksitya (Journal of Comprehensive Science, 2024)
The soil retaining wall is one of the reinforcements used to prevent landslides on the slope. Therefore, in planning, good analysis and calculation are needed to be able to bear the burden safely. At the research site, there is a slope of the plengsengan that has only been built for one month and has experienced a landslide. To prevent more severe landslides on this slope, it is necessary to design appropriate and effective slope reinforcement. The analysis of the use of the right type of reinforcement and its design will be carried out in this study in accordance with the requirements of SNI geotechnical 8640:2017. The results of the study show that gravity-type soil retaining walls are more suitable to be applied to strengthen the river slope. The design that has been designed has met several stability, namely safety against bollards (FK boling = 2.4), safety against shear (FK shear = 3.71), and safety against soil carrying capacity (FK carrying capacity = 7.54). The overall slope stability was carried out with the help of the Rocscience Slide program and obtained a slope stability safety factor value of 1.933.